2009
DOI: 10.1002/art.24892
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the need for hip and knee replacement surgery. Part 1. A two‐stage cross‐cohort approach

Abstract: Objective. To explore inequalities in the need for hip/knee replacement surgery using a 2-stage cross-cohort approach. Methods. In the first stage, a small-area population-based survey, the Somerset and Avon Survey of Health, was used to provide a high-quality measure of need for hip/knee replacement using the New Zealand (NZ) score. Receiver operating characteristic curve analyses were used to validate a simplified NZ score, excluding information from clinical examination. In the second stage, a nationally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…In studies using general population cohorts (not specifically diagnosed as having OA), obesity (defined as a BMI of $30 kg/m 2 ) was associated with a 10-fold higher risk of knee replacement (24), and a relative risk of 2.4 (95% CI 2.0-2.8) for the need for surgery based on pain, function, and clinical assessment (23). A Swedish study found similar results using a lower BMI cutoff ($25 kg/m 2 ), with an RR of 6.9 for women and 4.4 for men compared to subjects with a normal BMI (42).…”
Section: Discussionmentioning
confidence: 99%
“…In studies using general population cohorts (not specifically diagnosed as having OA), obesity (defined as a BMI of $30 kg/m 2 ) was associated with a 10-fold higher risk of knee replacement (24), and a relative risk of 2.4 (95% CI 2.0-2.8) for the need for surgery based on pain, function, and clinical assessment (23). A Swedish study found similar results using a lower BMI cutoff ($25 kg/m 2 ), with an RR of 6.9 for women and 4.4 for men compared to subjects with a normal BMI (42).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of total joint replacement represent only a fraction of the overall population with severe, symptomatic large joint OA. Among subjects over the age of 60 years in the UK, the prevalence of the need for total joint replacement (excluding those who actually receive total joint replacement) is between 12.4% and 16% (20, 21), and the prevalence of receipt of total joint replacement is ∼6% (20), which, when added to the prevalence of the need for total joint replacement, yields a prevalence of total joint replacement with or without receipt of surgery of between 18.4% and 22%. Thus, 27–33% of individuals who require a total joint replacement receive one.…”
Section: Discussionmentioning
confidence: 99%
“…Our results should be applicable to at least one‐fourth of individuals with severe, symptomatic large joint OA, which is a high enough proportion of such cases to be of merit and is consistent with the rates of transition from hip pain to being listed for total joint replacement (23%) in primary care patients over a 4‐year period in a prospective UK cohort study (22). Factors such as wealth, education, geographic region, smoking status, obesity, and sex (21, 23) have been reported to influence rates of access to total joint replacement, and recent studies have revealed considerable heterogeneity in the radiographic severity, functional disability, and pain in candidates for total joint replacement (24). Thus, for example, patients undergoing total joint replacement may be generally fitter than people with both clinically severe large joint OA and severe comorbidity, and our conclusions may not hold among nonsurgical severe large joint OA cases.…”
Section: Discussionmentioning
confidence: 99%
“…To identify whether or not a person is in need of joint replacement surgery in the ELSA data set, we used the New Zealand score out of 80, with a cutoff of 48 (19). Different choices of threshold will classify those with more/less severe disease as being in need of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described how a 2‐stage cross‐cohort approach can be used to identify people in need of hip and knee replacement and explored inequalities in the need for surgery (19). Briefly, the English Longitudinal Study of Ageing (ELSA) is a nationally representative population‐based sample of 11,392 people age ≥50 years living in private households in England.…”
Section: Methodsmentioning
confidence: 99%